Different Teaching Methods in Interactive Education and The Teacher’s Role - Barno Pulatovna Abdullaeva (Euro Asian Journal Publishing, 2024)
The article actualizes the various perspectives of the role of teachers in interactive learning, taking into account both how teachers plan the activities and their role in the instructional process with students. Interactive teaching is a promising strategy that poses a challenge to the professional service as well as teachers.
Keywords: teachers’ role; interactive teaching; interaction